Location and impact of the infarct-related artery in acute coronary syndrome: insight from the Swiss SPUM- ACS cohort. (14th October 2021) - Adjibodou, B; Obeid, S; Kraler, S; Denegri, A; Mach, F; Matter, C M; Nanchen, D; Roffi, M; Muller, O; Raeber, L; Luescher, T
Abstract: Background: Identifying the infarct-related artery (IRA) in patients with acute coronary syndromes (ACS) has prognostic and therapeutic implications. Purpose: We aimed to evaluate the distribution, clinical presentation and impact of the culprit lesion location on long-term outcomes in ACS patients treated with primary percutaneous coronary intervention, medication and secondary prevention according to Guidelines. Methods: Patients referred for ACS to one of the participating centres of the observational SPUM-ACS study between 2009 and 2017 with one year outcomes and independent events adjudication were included. The distribution of IRA, clinical presentation (STEMI/NSTEMI) and impact of IRA location on major adverse cardiac events (cardiac death, myocardial infarction, stent thrombosis, target vessel revascularisation) at one year were investigated. Results: 4'546 patients were included with 55% presenting as STEMI (mean age 62-years; 20% women), 42% as NSTEMI and 3% as unstable angina. The left anterior descending (LAD) artery was involved in 44.3%, the right coronary artery (RCA) and left circumflex artery (LCX) in 32.9% and 20%, respectively. Proximal and middle segments of the 3 main vessels were more often the culprit location compared to distal segments and side branches (78% versus. 22%). Left main (LM) and bypass graft were rarely involved (1.6% and 1.2% respectively), but most often responsible to overall cardiac dysfunction (higher NT-proBNP and hs troponin levels). Patients with an occluded IRA at angiography usually presented as STEMI on ECG (100% for LM, 90.5% for LAD territory, 83.8% for RCA territory, 56.6% for LCX territory). However 43.1% of patients with occluded LCX presented as NSTEMI. These patients were prone to extensive cardiac damage and significantly higher hs troponin levels as compared to those with patent LCX or STEMI presentation (626 ng/l vs 310 ng/l and 626 ng/l vs 580 ng/l respectively, p<0.001). Overall, 1-year MACE occurred in 11.8%. In native coronaries, the location of IRA had no impact on outcomes (20% LM, 10.9% LAD, 11.8% RCA, 11.8% LCX, p=0.112). However, in NSTEMI-ACS there were twice as many events when the LM was the IRA (MACE 20%, p=0.023) and 3-times higher when a bypass-graft was the IRA (33.9%, p=0.0001). Conclusions: ST elevations are highly suggestive of an occluded IRA. However more than 40% of patients presenting with ACS involving an occluded LCX did not demonstrate ST-elevation and were prone to extensive cardiac damage, urging the necessity for early invasive measures in these patients. In native coronaries the IRA location did not affect outcomes except in NSTEMI with LM involvement or ACS with bypass grafts as IRA that had much worse outcomes. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): - Swiss National Research Foundation - Zurich Heart House